Comparative techno-economic assessment of biomass and coal with CCS technologies in a pulverized combustion power plant in the United Kingdom. (December 2015) - Al-Qayim, Khalidah; Nimmo, William; Pourkashanian, Mohammed
Highlights: BECCS using white wood pellets oxy-fuel is more cost-effective than PCC technology. Assessment of cost of CO2 avoidance vs CO2 CCS indicates lower cost for CCS. For large scale BECCS deployment more CP and ROC government incentives needed. Abstract: The technical performance and cost effectiveness of white wood pellets (WWP) combustion in comparison to three types of coal namely U.S., Russian and Colombian coals are investigated in this study. Post-combustion capture and storage (CCS) namely with amine FG+, and oxy-fuel with carbon capture and storage (oxy-fuel) are applied to a 650 MW pulverized combustion (PC) plant. The impacts of the Renewable Obligation Certificate (ROC) and carbon price (CP) policy in accelerating the CCS deployment in the framework of GHG emissions mitigation, are also evaluated. The operational factors affecting CCS costs and emissions in the power generation plants are taken into consideration, hence, the Integrated Environmental Control Model (IECM 8.0.2) is employed for a systematic estimation of plant performance, costs and emissions of different scenarios of fuel and CCS technologies. This study showed that the utilization of white wood pellets (WWP) in electricity generation can annually avoid about 3 M tonnes CO2 emissions from a 650 MW power plant. However, this mitigation process had impact on the plant efficiency and the cost of electricity. Further, the BECCS using white wood pellets has showed a better efficiency and lower cost of electricity with the oxy-fuel technology than the post-combustion CCS technology. However, in order to boost biomass energy CCS (BECCS) deployment with the WWP, an increase of the ROC for biomass power plants, or, an increase of the carbon price for the coal power plants is recommended. It was found that, the sensitivity of COE towards the ROC was higher than towards the carbon price variation. This result can be interpreted as the ROC has more positive impact than the carbon price, on the COE from the point of customers view without adding more burdens on the power generation companies.